Themed Restaurant Examination to Improve Student’s Knowledge and Skills in Food and Beverage Management Class - Yulius, Kevin Gustian (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The paper emphasizes the importance of practical knowledge and hands-on experiences in hospitality education, particularly in food and beverage management. Themed events provide a platform for students to apply their theoretical knowledge, develop practical skills, and face real-world challenges. The event, centered around the culinary heritage of Tuscany, showcased student creativity and attention to detail. The event was successful overall, with positive guest feedback and student committee evaluations. However, areas for improvement were identified, including coordination issues, delays, and food quality inconsistencies. These findings highlight the need for better planning, coordination, and attention to detail in future events. In conclusion, the event provided valuable experiential learning for hospitality management students, allowing them to apply knowledge, develop skills, and navigate challenges. While the event showcased student capabilities, areas for improvement were identified, emphasizing the importance of continuous enhancement in execution and attention to detail. This research contributes to understanding the effectiveness of themed events and experiential learning in hospitality education, informing future improvements in preparing students for internships and careers in the industry.